European travels are a source for the history of the Arab world Dr. Shaw's travel is a model - saadi, khemissi (The Algerian Historical Journal, 2026)
One of the important sources that researchers and historians refer to in recent studies is trips and travels due to the news and information they carry that are useful in writing history, and in this regard, modern and contemporary European trips to the Arab world are a source of great importance. In this article, we want to know the reasons for European travels, their goals, their importance, examples of them and to what extent they can be relied upon in the process of historical writing, and we presented an example for that, which is Dr. Shaw's travel. In the end, we concluded by evaluating the process of relying on trips in the process of historical writing, after critiquing and evaluating them and ensuring the validity of the information contained therein.